Políticas públicas y su incidencia en la inclusión laboral de funcionarios con capacidades especiales del gobierno autónomo descentralizado municipal de quevedo, 2023 - Vera Rojas, Viviana Mariana (2025)
This study focuses on Public Policies and their impact on the labor inclusion of officials with special abilities of the Autonomous Decentralized Municipal Government of Quevedo" has the general objective of evaluating the influence of public policies on the labor inclusion of people with disabilities in the Municipal GAD of Quevedo. Through this research, we seek to evaluate the impact of public policies on the labor inclusion of officials with special abilities of the Autonomous Decentralized Municipal Government of Quevedo, 2024. This approach allows us to comprehensively address the various dimensions that affect the inclusion of people with disabilities in the workplace. The methodology used in this research combines deductive and synthesis methods to analyze the current context of labor inclusion. Various data collection techniques were applied, including observation guides, interviews, and surveys. This allowed us to collect both qualitative and quantitative information, facilitating an accurate diagnosis of the barriers and facilitators that employees face in their work environment. The results show both progress and challenges in the implementation of inclusive policies. It is highlighted that significant barriers persist, such as the lack of adequate training for staff. Concluding that there is a need for strategies to improve the current situation, recommendations that identify specific actions to strengthen inclusion and ensure that public policies do not only exist on paper, but are transformed into real opportunities.